2020
DOI: 10.3724/sp.j.1042.2020.01836
|View full text |Cite
|
Sign up to set email alerts
|

孤独感和手机成瘾的关系:一项元分析

Abstract: Bruggeman, H., van Hiel, A., van Hal, G., & van Dongen, S. (2019). Does the use of digital media affect psychological well-being? An empirical test among children aged 9 to 12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The reliability index and cultural adaptation of the scale applied in research of Chinese samples are well. 49 , 51 , 52…”
Section: Methodsmentioning
confidence: 99%
“…The reliability index and cultural adaptation of the scale applied in research of Chinese samples are well. 49 , 51 , 52…”
Section: Methodsmentioning
confidence: 99%
“…Among them, mobile phone addiction is one of the most common negative outcomes ( 6 , 7 ). Mobile phone addiction would lead to poorer self-regulation, attentional control, and inhibitory control than normal individuals ( 8 ). Research has shown that about 21.3% of Chinese college students suffer from mobile phone addiction ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phone addiction would have a negative impact on the individual's physiology, psychology, and behavior (He and Xia, 2021). A meta-analysis conducted by Zhang and Li (2020) on the relationship between loneliness and mobile phone addiction showed that there was a moderate positive correlation between mobile phone addiction and loneliness. Based on the above analysis, this study proposed that problematic mobile phone use played a mediating role between family functioning and loneliness (Hypothesis 2).…”
Section: Introductionmentioning
confidence: 99%